Secured knowledge sharing and creation using RBAC model for e-village - Usino, Wendi; Mantoro, Teddy; Ayu, Media Anugerah; Harjanto, Nazir (North Atlantic University Union (NAUN), 2012)
This paper introduces a Role Based Access Control (RBAC) model for e-Village in creating and sharing knowledge in a secure way. This includes secure information about marketing to help the products become an innovation and highly valuable. As a case study, the Pasir Region, East Kalimantan, has the 100 families who moved were originally from Jepara in order to enhance their living standard, as encouraged by the Indonesian Government. Jepara is a very famous area of craft products and carving furniture. The problem is that they have to change their livelihood from a crafter to a farmer and lack the necessary original skills. It also discusses and analyses the secure knowledge sharing and knowledge creating using e-village, not only for supporting the market development but also preserving the village culture more, especially in crafting and carving furniture. This study shows that the RBAC of e-village contributes significantly to the quality of knowledge for people in a remote area such as the Pasir Region village.